Cortical encoding of rhythmic kinematic structures in biological motion - Li Shen; Xiqian Lu; Xiangyong Yuan; Ruichen Hu; Ying Wang; Yi Jiang (NeuroImage, 2023)
Biological motion (BM) perception is of great survival value to human beings. The critical characteristics of BM information lie in kinematic cues containing rhythmic structures. However, how rhythmic kinematic structures of BM are dynamically represented in the brain and contribute to visual BM processing remains largely unknown. Here, we probed this issue in three experiments using electroencephalogram (EEG). We found that neural oscillations of observers entrained to the hierarchical kinematic structures of the BM sequences (i.e., step-cycle and gait-cycle for point-light walkers). Notably, only the cortical tracking of the higher-level rhythmic structure (i.e., gait-cycle) exhibited a BM processing specificity, manifested by enhanced neural responses to upright over inverted BM stimuli. This effect could be extended to different motion types and tasks, with its strength positively correlated with the perceptual sensitivity to BM stimuli at the right temporal brain region dedicated to visual BM processing. Modeling results further suggest that the neural encoding of spatiotemporally integrative kinematic cues, in particular the opponent motions of bilateral limbs, drives the selective cortical tracking of BM information. These findings underscore the existence of a cortical mechanism that encodes periodic kinematic features of body movements, which underlies the dynamic construction of visual BM perception.